Heterogeneous household responses to energy price shocks - Gert Peersman; Joris Wauters (National Bank of Belgium, 2022)
We use survey evidence on reported spending in hypothetical energy price shock scenarios to study novel features of the price elasticity of energy demand and the marginal propensity to consume (MPC) after paying the energy bill. We document several nonlinearities depending on the sign and magnitude of the energy price shock that are economically relevant, including at the extensive and intensive margins. There is also considerable heterogeneity across households. For price increases, the elasticity of energy demand appears to be significantly larger for households that will likely undertake major home renovations over the next months, and smaller for families with more appetite to consume. In contrast, MPCs depend on households' income, saving buffer, financial uncertainty, appetite to consume, and gender of household head. Yet household characteristics hardly matter when energy prices decline; we only find smaller MPCs for households with a greater saving buffer and younger families. Finally, we show that targeted price subsidies on energy for Belgian low-income households have been much more effective in supporting non-energy consumption than the general VAT reduction on energy prices.
Keywords: D12; E21; H31; Q41; Q43; 330; Energiekonsum; Energiepreis; Schock; Preiselastizität; Privater Konsum; Belgien